Ameliorant Formulation Utilization With Different Dose To Increase The Benthic Density In Peat Pond - Pamukas, Niken Ayu; ', Slamat; ', Syafriadiman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted from Mei –Juni 2016 the petani nenas street, Kualu Nenas, Districts Tambang, Kampar, Riau. Analyze parameters of quality soil, water and abundance of benthos species identification does at Environmental Quality Aquaculture Laboratory, Faculty of Fisheries and Marine Sciences, University of Riau. The aim of this research was to determine the effect of formulation ameliorant benthos abundance peat soil pool. The method used was an experimental method by using Completely Randomized Design (CRD) with one factor, six treatments and three replications. Treatments applied were P0: without ameliorant, P1: formulation ameliorant dose 400 gr/m2, P2: formulation ameliorant dose 600 gr/m2, P3: formulation ameliorant dose 800 gr/m2, P4: formulation ameliorant dose 1000 gr/m2 P5: formulation ameliorant dose 1200 gr/m2.The results showed that benthos abundance best is P4 (1000 g/m2) with abundance to 16.326 ind/m2 and got 9 benthos species from 4 classes that: Annelida, Molusca, and Insecta. Classes Annelida is 3 spesies, than Insecta class 1 spesies and Molusca class 5 species. The benthos species that got is Tubifex sp, Lumbriculidae sp, Trypanosillys zebra, Chironomus sp, Brotia sp, Melanoides sp, Thiara sp, Gyraulus sp and Pisidium sp.Keywords: Peat Soil, Ameliorant, Benthos Abundance